ROLE OF FORENSIC HISTOPATHOLOGY IN DIAGNOSING MEDICATION POISONING AT AUTOPSY: A CASE SERIES (Journal of Forensic Medicine & Toxicology, 2023)
Forensic histopathology is the application of histological techniques and examination to forensic pathology practice.1 Histopathology is usually done at autopsy to ascertain the cause of death, if macroscopic features are obscure, unreliable or unremarkable. Poisoning is a major cause of mortality and morbidity in India contributing a significant portion to the annual deaths and DALYs’. Deaths due to poisoning can sometimes be challenging and often attributable to the absence of significant macroscopic findings at autopsy. Frequently the toxicological analysis reports also, may not reveal the type of poison causing a serious challenge in formulating the cause and manner of death. We have presented two cases of deaths due to paracetamol and iron overdose and highlighted the importance of histopathology in identifying the type of poison. The cases mentioned in this article are those of medication poisoning
Keywords: Histopathology; Poisoning; DALY; Paracetamol; Iron